Understanding care and outcomes in adolescents and young adults with cancer: A review of the AYA HOPE study - Smith, Ashley Wilder (Pediatr Blood Cancer, 2018)
Historically, adolescents and young adults (AYA) diagnosed with cancer have been an understudied population, and their unique care experiences, needs, and outcomes were not well understood. Thus, 10 years ago, the National Cancer Institute supported the fielding of the Adolescent and Young Adult Health Outcomes and Patient Experiences (AYA HOPE) study to address this gap. We recruited individuals diagnosed at ages 15 to 39 with germ cell, Hodgkin and non-Hodgkin lymphoma, acute lymphoblastic leukemia, and sarcoma from Surveillance, Epidemiology, and End Results cancer registries into the first multicenter population-based study of medical care, physical, and mental health outcomes for AYAs with cancer in the United States. This review of the 17 published manuscripts showed low awareness of clinical trials and substantial impact of cancer on financial burden, education and work, relationships and family planning, and physical and mental health. It highlights the feasibility of a longitudinal population-based study and key lessons learned for research on AYAs with cancer in and beyond the United States.